2018
DOI: 10.1007/s11682-018-9926-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of machine learning algorithms performance for the prediction of early multiple sclerosis from resting-state FMRI connectivity data

Abstract: Machine Learning application on clinical data in order to support diagnosis and prognostic evaluation arouses growing interest in scientific community. However, choice of right algorithm to use was fundamental to perform reliable and robust classification. Our study aimed to explore if different kinds of Machine Learning technique could be effective to support early diagnosis of Multiple Sclerosis and which of them presented best performance in distinguishing Multiple Sclerosis patients from control subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…In our study, we found that the linear SVM classifier achieved the best performance in all classification process, which suggested that the linear SVM was indeed a good classifier for fMRI data. This finding was consistent with majority of previous studies (Craddock et al, 2009 ; Wang et al, 2016 ; Saccà et al, 2017 ). For example, using the linear SVM classifier, patients with depression were successfully distinguished from healthy volunteers (R. Cameron Craddock), One recent study achieved high accuracy in object categories classification task using functional connections from task-related functional neuroimaging as features and SVM as the classifier.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, we found that the linear SVM classifier achieved the best performance in all classification process, which suggested that the linear SVM was indeed a good classifier for fMRI data. This finding was consistent with majority of previous studies (Craddock et al, 2009 ; Wang et al, 2016 ; Saccà et al, 2017 ). For example, using the linear SVM classifier, patients with depression were successfully distinguished from healthy volunteers (R. Cameron Craddock), One recent study achieved high accuracy in object categories classification task using functional connections from task-related functional neuroimaging as features and SVM as the classifier.…”
Section: Discussionsupporting
confidence: 94%
“…57,58 ML specifically for early diagnosis was specified by seven studies for the later onset degenerative conditions MS and RA. 48,[59][60][61][62][63][64] Other diagnostic applications included distinguishing coeliac disease from an at-risk group 65,66 and differentiating those who have complications in T1D. 67,68 Random forests and support vector machine most frequently utilised.…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, investigating sex differences at the level of BOLD fluctuation may reveal if there is strong evidence of sex differences. Recently, machine learning (ML) techniques have been used widely to perform classification and regression on neuroscience data (Al Zoubi, Awad, & Kasabov, 2018;Al Zoubi, Ki Wong, et al, 2018;Campbell et al, 2020;Cohen, Chen, Parker Jones, Niu, & Wang, 2020;Du, Fu, & Calhoun, 2018;Garner et al, 2019;Kazeminejad & Sotero, 2019;Saccà et al, 2019). Some works focused on using ML for classifying subjects into male and female using functional (Ktena et al, 2018;Zhang, Dougherty, Baum, White, & Michael, 2018) and structural data (Chekroud et al, 2016;Feis, Brodersen, von Cramon, Luders, & Tittgemeyer, 2013;Rosenblatt, 2016).…”
Section: Introductionmentioning
confidence: 99%